Effects of dietary n-6/n-3 PUFA ratio on growth performance and lipid metabolism in nursery pigs - Guo, Junjie; Chen, Xiaoqian; Zhu, Huiling; Xiao, Kan; Zhang, Yanbing; Zhao, Shiwei; Chen, Guoshun; Liu, Yulan (Frontiers in Veterinary Science, 2025)
The proportion of n-6 and n-3 polyunsaturated fatty acid (PUFA) in commercial pig feed is severely unbalanced. This study was conducted to investigate the effects of different n-6/n-3 PUFA ratios on growth performance and lipid metabolism of nursery pigs. A total of 240 nursery pigs (Duroc × Large White × Landrace) were fed diets with different n-6/n-3 PUFA ratios, including 10:1, 5:1, 3:1, and 1.5:1. Pigs fed diet with n-6/n-3 PUFA ratio of 1.5:1 or 3:1 had optimum average daily gain and feed to gain ratio (p < 0.05). The levels of serum lipids including total cholesterol, triglyceride, high density lipoprotein and low density lipoprotein were the lowest in pigs fed diet with n-6/n-3 PUFA ratio of 1.5:1 (p < 0.05). The concentrations of serum insulin, adiponectin and leptin were the highest in pigs fed diet with n-6/n-3 PUFA ratio of 3:1 (p < 0.05). Pigs fed diet with n-6/n-3 PUFA ratio of 3:1 had the highest abundance of genes associated with fatty acid absorption and transportation (FATP4, and PPARγ), synthesis and storage (FAS and GPAT) and degradation (ATGL, HSL, and MAGL) in intestine (p < 0.05). Pigs fed diet with n-6/n-3 PUFA ratio of 1.5:1 had the lowest abundance of genes associated with fatty acid absorption (CD36 and FABP4), synthesis and storage (ACC, FAS, ACLY, PAP, AGPAT, and GPAT) and degradation (CPT1 and HSL) in gastrocnemius muscle (p < 0.05). The mRNA expression of genes associated with fatty acid metabolism (FATP2, FATP5, FABP1, FABP4, LPL, ACS, ACLY, AGPAT, GPAT, CPT1, ATGL, and MAGL) was up-regulated in liver and subcutaneous fat of pigs fed diet with n-6/n-3 PUFA ratios of 1.5:1–5:1 (p < 0.05). In summary, diets with lower n-6/n-3 PUFA ratios improve growth performance, reduce blood lipids, facilitate lipid metabolism in intestine, liver and subcutaneous fat, and inhibit fatty acid absorption, synthesis and storage in gastrocnemius muscle in pigs.